Criminal Aspects of Passive Vote Buying in the Conduct of General Elections in Indonesia - Nesti Yusticiadewi Alakaman; Julianus Edwin Latupeirissa; Denny Latumaerissa (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
In the process of conducting general elections, there are often actions that disrupt democratic order, and in reality, many violations lead to a decline in general election quality; one key issue is money politics, especially vote buying. Data, surveys, and documented cases show that those who make promises, offer money, or provide other material incentives (active vote buying) are more often prosecuted than the recipients (passive vote buying) during general elections. This issue is linked to the lack of regulations that address passive vote buying. The purpose of this article is to examine and analyze the forms of money politics in the conduct of general elections and the measures of legal enforcement in the act of passive vote buying. This article uses a normative legal research, with a statutory approach, a case approach, and a conceptual approach. The results of the research show that 1. The forms of money politics in general elections include various types, such as vote buying, vote brokers, political corruption, serangan fajar, mass mobilization, and money politics at different levels: upper, middle, and lower; 2. The efforts of law efforcement to address passive vote buying involve applying Article 149 paragraphs (1) and (2) of the Indonesian Criminal Code, which clearly covers both active and passive vote buying, and it also aim to reform criminal law by regulating both active and passive vote buying in future general election law (ius constituendum).